Pengaruh Kesadaran Wajib Pajak, Sosialisasi Perpajakan dan Pemahaman Perpajakan terhadap Kepatuhan Wajib Pajak UMKM di Kecamatan Karawaci Kota Tangerang - Adinda Nurhaliza Azzahra; Maman Darmansyah (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Tax compliance among Micro, Small, and Medium Enterprises (MSMEs) remains a persistent challenge in Indonesia, particularly due to low awareness, limited tax socialization, and inadequate understanding of tax regulations. This condition contributes to the gap between potential and actual tax revenue from the MSME sector. This study aims to examine the effect of taxpayer awareness, tax socialization, and tax understanding on MSME taxpayer compliance in Karawaci District, Tangerang City. The research employs a quantitative explanatory approach using primary data collected through structured questionnaires. A total of 104 MSME taxpayers were selected as respondents based on purposive sampling criteria. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 27, supported by descriptive statistics, data quality tests, classical assumption tests, and hypothesis testing. The results reveal that taxpayer awareness, tax socialization, and tax understanding each have a positive and significant effect on MSME taxpayer compliance, both individually and simultaneously. These findings indicate that improving tax literacy through effective education programs, consistent tax socialization, and strengthening taxpayers’ internal awareness can enhance voluntary tax compliance among MSMEs.